Pros and cons of incomplete contract in Private Finance Initiative (PFI) Project - Mansor, Syaimasyaza; Abdul Rashid, Khairuddin; Ayob, Mohd Fairullazi; Hasan, Sharina Farihah (Future Academy, 2019)
A contract is incomplete when it did not clearly spell out among others the parties’ responsibilities and duties for all realized contingency and it contain loophole, some provisions being left out, and the wording used contain element of vagueness. Incomplete contract is said to be inevitable especially for projects with lengthy contract period, a lot of risk and/or uncertainty, such as Private Finance Initiative (PFI) projects. IC has both its PROs (positive) and CONs (negative) implications. Flexibility to deal with uncertainty when it arises is the PROs of IC while the CONs are inefficiencies and costs, contract amendment and others. PFI is among the key alternative procurement used in Malaysia. However, there has been criticism about PFI e.g. lopsided contractual agreement, absence of robust and transparent agreement, and vagueness in terms of sustainable element. Based on the issues mentioned, it is therefore,significant to carry out this research to assess the PROs and CONs implications of IC in PFI projects. Research method begin with literature review and followed by two rounds of Modified Delphi method. 18 and 13 panellists involved in the MD. The results from the research have identified eight (8) PROs and six (6) CONs. Findings of the research are significant for the improvement of future PFI project whereby PFI stakeholders can come out with proper action to deal with implications of IC.